Pemakaian Temporary Tower untuk Optimalisasi Penyelesaian Rekonduktoring dan Penggantian Tower Saluran Udara Tegangan Tinggi (SUTT) 150 KV - Muhammad Iqbal; Haryo Dwito Armono (Rekayasa, 2023)
The use of temporary towers is a solution to shorten the outage time. Temporary Tower is used as a tool in reconductoring work and tower replacement. The study by calculating the Budget Plan Cost (RAB) and schedule analysis using Microsoft Project Application to determine the comparative duration of time required to complete the reconductoring work and tower replacement between using temporary tower and without temporary tower. From the time schedule created, it will be known which work method uses a shorter duration of time so that it can save or speed up the outage time. This study will produce what kind or type of conductor is appropriate in the context of replacing conductors or reconductoring SUTT 150 kV A - C, resulting in a reconductoring and tower replacement work schedule that is 15 days faster when using a temporary tower and reduces the outage time by about 132 days or about -89%. However, it requires an additional cost of Rp 1,872,217,454, which is still much smaller than the loss due to outages if the work is not done with a temporary tower.